IMPLEMENTASI ALGORITMA NAÏVE BAYES PADA SISTEM PAKAR DIAGNOSA PENYAKIT TIFOID BERBASIS WEB - Ilham Budiman; Ferdiansyah (JURNAL ILMIAH BETRIK, 2022)
Typhoid is an infectious disease that is still a health problem in developing countries, especially in Indonesia. Salmonella typhi is a bacterium that causes typhoid fever which can be transmitted through food or drink contaminated with feces or urine from an infected person. The first step in the management of typhoid is the establishment of an appropriate diagnosis. The expert system application for diagnosing diarrheal disease is made with a web-based application, so that it can be accessed by the wider community, besides this application can also help medical personnel to make decisions in the diagnosis of typhoid. The advantage of the nave Bayes algorithm in this expert system is that it can increase calculations ranging from nausea and vomiting, diarrhea, sore throat, headache, fever and loss of appetite, so obtained 14 rules resulting from interviews with experts, so it can be concluded that the research conducted implemented into a web application can assist users in diagnosing typhoid disease in each patient.